2023
DOI: 10.3390/nu15163624
|View full text |Cite
|
Sign up to set email alerts
|

Effects of an Eating Pattern Including Colorful Fruits and Vegetables on Management of Gestational Diabetes: A Randomized Controlled Trial

Kataryna Jaworsky,
Pamela DeVillez,
James M. Alexander
et al.

Abstract: Gestational diabetes mellitus (GDM), defined as abnormal glucose tolerance that presents during the second and third trimesters of pregnancy, is a growing issue in the United States and worldwide. If left untreated or poorly controlled, GDM can result in numerous consequences for both the mother and the fetus; thus, it is imperative that different avenues of management for GDM be explored. There is a paucity of studies that examine how lifestyle changes, including dietary and physical activity, affect manageme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 43 publications
0
2
0
2
Order By: Relevance
“…A partir desses pontos, recente estudo randomizado comparou o perfil cardiometabólico de 38 mulheres que receberam apenas educação nutricional, com aconselhamento dietético sobre alimentação saudável (controle), ou foram alvo de uma intervenção nutricional (experimento), com aumento do consumo de uma xícara de frutas vermelhas e uma xícara de vegetais de folhas verdes, seguido de caminhada após as refeições ao longo de 12 semanas. A avaliação das variáveis do estudo se deu por meio de amostras de sangue, medidas antropométricas e dados da dieta e das atividades físicas, coletados no início e no final do estudo em ambos os grupos (JAWORSKY et al, 2023).…”
Section: Resultsunclassified
See 1 more Smart Citation
“…A partir desses pontos, recente estudo randomizado comparou o perfil cardiometabólico de 38 mulheres que receberam apenas educação nutricional, com aconselhamento dietético sobre alimentação saudável (controle), ou foram alvo de uma intervenção nutricional (experimento), com aumento do consumo de uma xícara de frutas vermelhas e uma xícara de vegetais de folhas verdes, seguido de caminhada após as refeições ao longo de 12 semanas. A avaliação das variáveis do estudo se deu por meio de amostras de sangue, medidas antropométricas e dados da dieta e das atividades físicas, coletados no início e no final do estudo em ambos os grupos (JAWORSKY et al, 2023).…”
Section: Resultsunclassified
“…Após as 12 semanas, a análise dos dados (figura 3) pelos autores demonstrou que a intervenção dietética, com incentivo ao consumo de frutas vermelhas e vegetais folhosos, demonstrou melhora do controle glicêmico e de outros parâmetros metabólicos e inflamatórios, como diminuição de interleucina-6 e aumento de HDL e da capacidade antioxidante sérica total, em comparação com o grupo controle (JAWORSKY et al, 2023).…”
Section: Resultsunclassified
“…[44][45][46] It has also been shown that dietary fiber supplementation during pregnancy in Chinese women of advanced maternal age does not reduce the incidence of GDM, but improves glucose metabolism, gestational weight gain, and preterm delivery. [47] Although a diet high in dietary fiber can help prevent and treat GDM, it is inconsistent in its requirements, including 9.5 g dietary fiber/d, [48] Consume one cup of whole berries and one cup of leafy greens per day, [49] 24 g dietary fiber/d. [50] Beans, fruits, whole grains and vegetables rich in dietary fiber may reduce the risk of GDM, [51][52][53] whereas excess consumption of fruits, potatoes and fruit juices is associated with an increased risk of GDM.…”
Section: Polyunsaturated Fatty Acidmentioning
confidence: 99%
“…Dietary macronutrients have also been linked to increasing GDM risk including the consumption of low fiber, high glycemic index diets [12] and low carbohydrate, high-fat diets [13]. Of late a whole host of dietary strategies have been or are being studied to investigate potential links with alterations in GDM risk, including variations of the Mediterraneanstyle diet [14,15], high-fiber diets [16], diets with high complex carbohydrate contents [17], plant-based dietary patterns [18], diets high in probiotic yogurt contents [19], and diets with high colorful fruit and vegetable contents [20]. Further, observational dietary studies have reported associations between GDM risk and protein intake in early pregnancy (higher risk with increased early animal protein intakes and lower risk with increased early plant protein intakes [21]).…”
mentioning
confidence: 99%